Chronological Analysis and Remote Sensing of Craters on the Surface of Mars - Howari, Fares M.; Sharma, Manish; Xavier, Cijo M.; Nazzal, Yousef; AlAydaroos, Fatima (Frontiers in Environmental Science, 2021)
In the present research, we had carried out the detailed chronological and compositional analysis along with the detailed spectral analysis of three unnamed craters on the surface of Mars. Knowledge on chronology/age analysis and compositional analysis of Mars surface is essential for future manned and unmanned missions. The study area is near the landing site of previous landed missions, which could be used for future landing. The area is interesting to be studied because of having high elevation in north-eastern side and low elevation in southern side, consisting of three major geological boundaries i.e. hesperian, noachian and amazonian, which is been further subdivided into fourteen units. Chronological investigations carried out using active machine learning approach and Craterstats 2.0 software, which revealed the age plot 3.09 ± 0.04 Ga for amazonian, 3.63 ± 0.0 Ga for hesperian and 3.73 ± 0.0 Ga for noachian geological unit stating N(1) craters density corresponds to early amazonian, early hesperian and late noachian/early hesperian period according to the established crater density boundaries respectively. Compact Reconnaissance Imaging Spectrometer for Mars (CRISM) derived browse-products is used for compositional study and surface characteristics of Mars. Spectral investigation of unnamed crater belongs to amazonian period, shown to be majorly composed of oxides as primary mineral, indicating the spectra of hematite, bohmite and akaganeite. Hesperian unit unnamed crater shown the signature of monohydrated sulphates, melilite, Illite and kaolinite minerals in the region. For the unnamed crater 3, which belong to noachian period have diagnostic absorptions of clay minerals in their extracted spectra, indicating the sign of long-term water-rock interactions in the period. Derived chronology results and compositional study of craters help to better understand the geological formation units of Mars surface.